Convolution operators in A −∞ for convex domains - Abanin, Alexander V. (2013)
We consider the convolution operators in spaces of functions which are holomorphic in a bounded convex domain in ℂn and have a polynomial growth near its boundary. A characterization of the surjectivity of such operators on the class of all domains is given in terms of low bounds of the Laplace transformation of analytic functionals defining the operators.